The gut microbiota as a biomarker in epilepsy - Emilio Russo (Neurobiology of Disease, 2022)
Biomarkers are defined as objectively measurable variables of a biologic process, either physiologic or pathologic, that provide reliable information on the status of that specific process in a specific moment. Validated biomarkers in epilepsy research represent an urgent unmet need being essential to improve research quality; as an example, biomarkers in epileptogenesis identifying these subjects at risk to develop epilepsy after an initial insult definitively would lead to an improvement in clinical studies to find antiepileptogenic drugs. The gut microbiota (GM) has recently encountered the interest of neuroscience which confirmed its clear involvement in several neurological disorders. GM's role in epilepsy has only recently been studied, however, interesting results are already available. Besides the interest in GM as a suitable therapeutic target and a few preclinical and clinical studies indicating the potential antiseizure effects of GM manipulation, microbiota composition has been found altered in patients with epilepsy as well as some animal models. Only few studies have tried to analyse GM composition as a suitable biomarker and, despite very promising, several drawbacks limit our understanding. On the other hand, GM composition may be useful in discriminating drug-resistant from drug-responsive patients at any stage or patients at risk of developing epilepsy after an insult. The main limitation in the area is the lack of large studies in homogeneous patients and standardization is a must for a proper understanding. Finally, considering the number of variables coming both from epilepsy and GM, big data analysis as in the case of genetics should be considered.